Fostering Creativity to Enhance Physics Achievement: An Analysis of the Relationship Between Creative Thinking Ability and Student Learning Outcomes - Muhammad Amin Said; Ilham, Ilham; Muhammad Fakhrul Abdul Kadir (Universitas Negeri Semarang, 2024)
The ability to think creatively is crucial for improving students' learning outcomes. However, in reality, many students whose learning outcomes are low and do not meet the minimum competency criteria. Therefore, this research aims to determine the relationship between creative thinking ability and physics learning outcomes. The study employed survey methods with a correlational approach. The population of this study included 248 students from the XI MIPA class at State Senior High School 9 Gowa. The sample was drawn through simple random sampling, totaling 105 students. The instruments used in this research comprised tests measuring creative thinking and learning outcomes. Descriptive analysis results indicated that the average score for creative thinking ability was categorized as moderately creative, while the average score for learning outcomes was deemed good. The conclusion of this research revealed a significant, positive correlation between creative thinking ability and physics learning outcomes in elasticity and Hooke's law among the XI-grade students. This research may encourage teachers to create more creative learning environments.